Pelaksanaan Pelayanan Pemerintah Nagari dalam Memenuhi Kebutuhan Informasi Masyarakat (Studi kasus pelayanan informasi Pemerintah nagari alahan nan tigo, kecamatan Asam Jujuhan, Dharmasraya) - Sumarni, Yesi; Darwis, Yuliandre (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Information services in meeting the needs of the community in the Alahan Nan Tigo village, especially information needs, have been implemented according to the principles, mechanisms and forms of information services that should be provided. The government of Alahan Nan Tigo village has implemented SOPs and principles of information services to balance current developments in information technology and take into account the conditions and knowledge of the people of the village. This is proven by the mechanisms and forms of service carried out openly, whether through communication technology media such as social media. , online media or directly with the respective heads of jorong who are responsible for this.